PENGARUH KOMITMEN GURU DAN STRATEGI PEMBELAJARAN TERHADAP PRESTASI DAN MUTU SEKOLAH PADA SEKOLAH DASAR ISLAM TERPADU DI KABUPATEN SUMENEP - Alvin Arifin (Adaara: Jurnal Manajemen Pendidikan Islam, 2020)
This study examines the effect of teacher commitment and learning strategies on school achievement and quality in integrated Islamic elementary schools in Sumenep district. This research is a quantitative study. Data collection techniques by giving questionnaires to teachers. The population of this research is all teachers who teach in integrated Islamic elementary schools in Sumenep Regency with a sample of 46 teachers. The analysis used is descriptive analysis and partial least square analysis with SmartPLS software. The results of this study indicate that teacher commitment and student achievement have a positive and significant effect on school quality. Learning strategies do not have a direct influence on school quality. Teacher commitment and learning strategies have a positive and significant effect on achievement. Achievement mediates the effect of teacher commitment on school quality significantly. Achievement does not mediate the effect of learning strategies on school quality.